CORPOREIDADE: A POSSIBILITY IN THE CHANGE OF VALUES (Fiep Bulletin - online, 2014)
This work considers to analyze the corporeidade to break conceptions and scientific values of the rationality. In this thought, the manipulation was destined to the bodies that do not have the scientific aspect of our society and the standard desired in the education, physical education and sport. With this, the mind won the body, symbolized for the competitive auto-affirmative behavior, that revealed in the social environment for the glorious dispute of that they are inside of this process and discriminating all the other bodies that did not have the same image. The proposal of change of paradigm of reformularization of the values is a possibility anchored in the estimated ones of the deep ecology of Capra (1999), of a balance of values. Of this form, the deep ecology in will take them in the balance of the integrativas perceptions and auto - affirmative, of the diversity in general in favor of a system that it makes possible a harmoniosidade enters the human beings in general.
Keywords: Corporeidade; Physical Education; Preconception